THE SUSTAINABLE AGRICULTURE SUPPLY CHAINS: A BIBLIOMETRIC ANALYSIS APPROACH - Zuhri, Nur Muttaqien; Nurcahyono, Nurcahyono; Puspita, Nurul (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The resilience and effectiveness of agricultural supply chains are widely recognized in supply chain management. Despite continuous advancements in environmental considerations and the competitiveness and effectiveness of supply chains, there needs to be a thorough evaluation in the literature regarding the influence of sustainable agricultural supply chains on these aspects. This study employs bibliometric analysis to explore sustainable agricultural supply chains, emphasizing essential aspects of supply chain effectiveness and the impact of a dynamically evolving environment. It bridges the divide between environmental science fields and agroindustry. Using the PRISMA VOSviewer methodology for bibliometric evaluation, Eight hundred sixty-one academic papers were meticulously chosen and examined using a thorough method that combines bibliometric and descriptive analysis. The comprehensive literature review uncovers the intricate and interconnected relationship between supply chain performance and sustainable agriculture, emphasizing the importance of promoting sustainability in a competitive business environment within a dynamic landscape. The research expands existing understanding by pinpointing seven clusters and comprehensively summarizing the present research environment. The primary themes and areas of interest in sustainable agricultural supply chains include food security, life cycle assessment, performance, blockchain, and energy. This research sets the course for future academic exploration in this crucial field and presents valuable perspectives for practitioners. The research highlights. The significance of incorporating sustainable methods within agricultural supply chains to enhance sustainability in today's quickly changing business environment, focusing on environmental and social aspects.